2009
DOI: 10.1182/blood-2009-02-202937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mycophenolate mofetil for initial treatment of chronic graft-versus-host disease

Abstract: We conducted a double-blind, randomized multicenter trial to determine whether the addition of mycophenolate mofetil (MMF) improves the efficacy of initial systemic treatment of chronic graft-versushost disease (GVHD). The primary endpoint was resolution of chronic GVHD and withdrawal of all systemic treatment within 2 years, without secondary treatment. Enrollment of 230 patients was planned, providing 90% power to observe a 20% difference in success rates between the 2 arms. The study was closed after 4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
2
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 41 publications
(63 reference statements)
0
118
2
5
Order By: Relevance
“…A retrospective study of de novo and steroid-refractory cGVHD has shown response rates of 90 and 75 %, respectively [139]. In a randomized prospective trial of MMF vs placebo in addition to other treatment for cGVHD, the study was terminated early due to no difference in response rate in control and study arms [140]. Common side effects of MMF include cytopenias, infections and gastrointestinal toxicity which can mimic aGVHD.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…A retrospective study of de novo and steroid-refractory cGVHD has shown response rates of 90 and 75 %, respectively [139]. In a randomized prospective trial of MMF vs placebo in addition to other treatment for cGVHD, the study was terminated early due to no difference in response rate in control and study arms [140]. Common side effects of MMF include cytopenias, infections and gastrointestinal toxicity which can mimic aGVHD.…”
Section: Mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…Examples include daclizumab that seems effective in corticosteroid-resistant aGVHD but detrimental when added to corticosteroids as initial therapy or mycophenolate that is ineffective when added to steroids for the initial treatment of cGVHD. 87,88 Reasons for this are complex and incompletely understood. Its possible corticoisteroid-resistant cases of GVHD are biologically different than untreated cases.…”
Section: Pomalidomidementioning
confidence: 99%
“…O uso de micofenolato mofetil (MMF) associado ao tratamento inicial foi avaliado em estudo duplo-cego randomizado, 28 fechado em 2008, após análise de resposta (resolução de DECH-c) em 151 pacientes (23% -grupo MMF vs 18% -controles, NS). A comparação da taxa de retirada de imunossupressão em dois anos também não mostrou evidên-cia de benefício em associar o MMF ao esquema inicial para DECH-c (DIa).…”
Section: Tratamento Da Dech-c Moderada E Graveunclassified